Hypertonic media inhibit receptor-mediated endocytosis by blocking clathrin-coated pit formation (The Rockefeller University Press, 1989)
Two seemingly unrelated experimental treatments inhibit receptor mediated endocytosis: (a) depletion of intracellular K+ (Larkin, J. M., M. S. Brown, J. L. Goldstein, and R. G. W. Anderson. 1983. Cell. 33:273- 285); and (b) treatment with hypertonic media (Daukas, G., and S. H. Zigmond. 1985. J. Cell Biol. 101:1673-1679). Since the former inhibits the formation of clathrin-coated pits (Larkin, J. M., W. D. Donzell, and R. G. W. Anderson, 1986. J. Cell Biol. 103:2619-2627), we were interested in determining whether hypertonic treatment has the same effect, and if so, why. Fibroblasts (human or chicken) were incubated in normal saline made hypertonic with 0.45 M sucrose, then broken open by sonication and freeze-etched to generate replicas of their inner membrane surfaces. Whereas untreated cells display typical geodesic lattices of clathrin under each coated pit, hypertonic cells display in addition a number of empty clathrin "microcages". At first, these appear around the edges of normal coated pit lattices. With further time in hypertonic medium, however, normal lattices largely disappear and are replaced by accumulations of microcages. Concomitantly, low density lipoprotein (LDL) receptors lose their normal clustered distribution and become dispersed all over the cell surface, as seen by fluorescence microscopy and freeze-etch electron microscopy of LDL attached to the cell surface. Upon return to normal medium at 37 degrees C, these changes promptly reverse. Within 2 min, small clusters of LDL reappear on the surfaces of cells and normal clathrin lattices begin to reappear inside; the size and number of these receptor/clathrin complexes returns to normal over the next 10 min. Thus, in spite of their seeming unrelatedness, both K+ depletion and hypertonic treatment cause coated pits to disappear, and both induce abnormal clathrin polymerization into empty microcages. This suggests that in both cases, an abnormal formation of microcages inhibits endocytosis by rendering clathrin unavailable for assembly into normal coated pits.